Efektifitas Penggunaan Mobile Phone Text Messaging Pada Penderita Penyakit HIV/AIDS The Effectiveness Of Using Mobile Phone Text Messaging In Hiv / Aids Patients - Chintya Marethania Putri; Ade Nabila Rosda; Adelia Dwi Rizki; Atikah Rizky Amalia; Dinita Anggun P; Dwi Yuniarahmah; Elda Mariyani; Aprillia Veranita (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
HIV (Human Immunodeficiency Virus) is a virus that attacks the immune system and can weaken the body's ability to fight infection and disease. AIDS (Acquired Immune Deficiency Syndrome) is a condition in which HIV is already in the final stage of infection. Many of the HIV-infected patients do not adhere to treatment. The increase in this disease is supported by the emergence of various technologies that are increasingly developing, one of which is a Text Message for PLWHA (People With HIV AIDS) which is actually very supportive in the healing process of PLWHA where this technology emphasizes that patients can comply with ART (Antiretroviral Therapy) treatment the message will always be sent to the patient. However, this technology will run effectively if it is supported by several factors, namely the patient's own ability to receive the messages that have been conveyed in the writing of this article through a simple approach (simplified approach). Searching the article database using google scholar found 10 journals related to counseling. The journal is analyzed to prove its effectiveness. It can be concluded that telephone counseling can improve adherence to the use of Antiretroviral Therapy (ART) and suppress HIV increases, the use of text message-based mobile applications shows good results in the treatment of PLWHA, communication through text message-based technology with patients has been shown to significantly improve patient adherence. HIV and plasma viral load (PVL). However, all will be effective if supported by adequate infrastructure and support from other parties. The results of a literature study of 10 articles conducted by the author show that the use of technology by utilizing SMS services in the world of health for people with HIV / AIDS is proven to be effective.